Impact of Strength Training Intensity on Brain-derived Neurotrophic Factor - Borges Junior, Marcos; Tavares, Larissa Ferreira Jacomini; Nagata, Gabriela Yumi; Barroso, Lucélia Scarabeli Silva; Fernandes, Heliana Barros; Souza-Gomes, Antonio Felipe; Miranda, Aline Silva; Nunes-Silva, Albená (International Journal of Sports Medicine, 2023)
The present study employed a randomized crossover design to investigate the effect of strength-training exercise at varying intensities on acute changes in plasma brain-derived neurotrophic factor (BDNF) levels. Fourteen trained male subjects (41.0±5.8 years old) were enrolled in the current study. The strength-training protocol included bench press, leg press, and lat pull-down exercises. Participants performed four sets with repetition failure at 60% or 80% of their one-repetition maximum (1RM), with a two-minute rest period. The order of intensity was randomized among volunteers. Blood samples were collected before, immediately after, and one hour after each exercise protocol. A time-point comparison revealed that a single session of strength training at 60% of 1RM increased lactate plasma concentrations from 1.2 to 16 mmol/L (p<0.0001). However, no significant changes were observed in the plasma BDNF concentration. Conversely, the training session at 80% of 1RM increased lactate concentrations from 1.3 to 14 mmol/L (p<0.0001) and BDNF concentrations from 461 to 1730 pg/ml (p=0.035) one hour after the session’s conclusion. These findings support the hypothesis that a single strength-training session at 80% 1RM can significantly enhance circulating levels of BDNF.
Keywords: physical exercise; BDNF; strength training; intensity